Comportamento térmico em regime não-adiabático de nanopartículas superparamagnéticas sob ação de um campo magnético oscilante - Iglesias, Carlos Augusto de Moraes (2018)
The phenomena of raising the temperature of magnetic nanoparticles under an alternating magnetic field, known as magnetic hyperthermia, is an outstanding field, which gives rise to challenges in the context of fundamental physics and providing new roads to applications, such as in the cancer treatment and in the control of thermally activated drug delivery. Thus, the complete understanding of the behavior of these systems with reduced dimensions becomes a key point and the optimization of the production processes and the properties of these materials, a challenging task. In this work, we perform a theoretical and experimental investigation of the magnetic hyperthermia in MgO:F e2O3 and FeO:F e2O3 superparamagnetic nanoparticles. Specifically, we aim to fully understand the influence of the composition, nanoparticle size, as well as amplitude and frequency of the field on the specific absorption rate of the samples. Here, we propose a theoretical model to describe the thermal behavior of magnetic nanoparticles, providing further insights on well-known parameters found in literature. To test the robustness of the approach, we apply the theoretical model to describe the magnetic hyperthermia curves obtained experimentally. To obtain the magnetic hyperthermia curves, an experimental system is developed, making possible to generate magnetic fields with frequency up to 100 kHz and amplitude up to 200 Oe. The excellent agreement between theoretical and experimental results provides support to confirm the validity of our approach to describe the thermal behavior of magnetic nanoparticles.